Effect of the game design, the goal type and the number of players on intensity of play in small-sided soccer games in youth elite players - Gonzalez-Rodenas, J.; Calabuig, F.; Aranda, R. (Journal of Human Kinetics, 2015)
The aim of this study was to compare the effects of game design modification, the type of the goal and the number of players on the intensity of play in small-sided soccer games (SSGs) in youth elite players. Twenty young soccer players (age 13.7 ± 0.5 years, body mass 57.4 ± 7.8 kg, body height 1.67 ± 7.8 m, maximal heart rate 201.1 ± 8.2 beats/min) performed three types of SSGs (possession play (PP) vs. regular goals (RG) vs. small goals (SG)) in both four-a-side and six-a-side formats. The heart rate responses were recorded and analysed as an indicator of the intensity of play. The four-a-side format obtained higher intensity of play than six-a-side for PP (p<0.05), but not for SG and RG. SG showed higher intensity of play than RG for four-a-side (p<0.001), but not for six-a-side. PP registered higher intensity of play than RG (p<0.05), but not than SG in four-a-side, whereas in six-a-side no differences were found between the three formats. In conclusion, the modification of variables such as the number of players, the game design and the type of the goal influences the intensity of play in small-sided soccer games in youth players.